Early impact of rotavirus vaccine in under 5 year old children hospitalized due to diarrhea, Swaziland. Issue 47 (12th November 2018) - Maphalala, Gugu; Phungwayo, Nomcebo; Masona, Gilbert; Lukhele, Njabulo; Tsegaye, Getahun; Dube, Nomsa; Sindisiwe, Dlamini; Khumalo, Lonkululeko; Daniel, Fussum; Katsande, Reggis; Tate, Jacqueline E.; Mwenda, Jason M.; et al.
Abstract: Background: Swaziland introduced rotavirus vaccine in the National Immunization Program, in May 2015, with the objective of reducing the burden of rotavirus diarrheal disease. We monitored the early impact of the vaccine in reducing rotavirus diarrhea. Methods: We conducted sentinel rotavirus surveillance from January 2013 to December 2016 in children under five years of age admitted due to diarrhea attending Mbabane Government Referral Hospital in the Hhohho Region and Raleigh Fitkin Memorial Hospital in the Manzini Region. All cases had stool samples collected and tested for rotavirus antigen by enzyme immunoassay. Results: Between 2013 and 2016, 596 samples were collected and tested. Rotavirus positivity reduced from average of 50.8% (172/338) (in 2013–2014 (pre vaccine period)) to 29% (24/82) in 2016, post-vaccine introduction. The median age of children with rotavirus infection increased from average of 10 months in 2013–2014 to 13.7 months in 2016. The peak season for all-cause diarrhea and rotavirus-specific hospitalizations among children under five years of age was June–August in all years with a blunting of the peak season in 2016. Rotavirus positivity among children 0–11 months reduced from an average of 49% in 2013–2014 (116/236) to 33% (15/45) in 2016, a 33% reduction following rotavirus vaccine introduction. Conclusion: There has been a rapid reduction of all-cause diarrhea and rotavirus hospitalizations in Swaziland, particularly in young children and during the rotavirus season, after the introduction rotavirus vaccine. Continued surveillance is needed to monitor the long-term impact of rotavirus vaccine introduction.